Studi Fenomenologi Konsep Diri Sindhen dalam Pergelaran Wayang Kulit - Devitasari, Astrid (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the motivation and self-concept of a Sindhen before becoming a Sindhen, as well as during and after becoming a Sindhen. This research uses a qualitative method with a phenomenological approach that seeks an in-depth understanding of the meaning of events and their relationship to people in certain situations. The informants were selected using a purposive sampling technique with the following criteria: Sindhen, who lives in Banyumas Regency and has worked as a Sindhen for at least ten years. This research shows that there is no unique process to become a Sindhi. A person only has to have the intention and hard work to become a Sindhi, and there are no special rituals that a Sindhi must carry out. In conclusion, to be able to sing, someone can learn autodidactically jo, in a musical group, or watch cassettes. Keywords: Sindhen, Shadow puppets, Self Concept, Banyumas